Audio Recognition System Based on Emotion Using Deep Learning and AI - Balachandran, Swetha; Sharika Mohan, J.; Jeneefer, M.; Shanmugha Priya, M. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Human emotions are designed to help people understand each other and share their feelings and intentions. Emotions are expressed through both verbal and facial expressions. Music has a significant impact on an individual’s life. This is an innovative method that assists the user in automatically generating a playlist of music based on the user’s mood. A web camera is used in this system to identify the user’s mood by looking at their facial expressions. Once the mood is identified, the algorithm offers a playlist for that mood, saving the user a lot of time over manually selecting and enjoying songs. It also includes a basic plan for collecting user information such as playlist creation, emotion classification, and interest level, as well as reorganizing the playlist.